Calves as Main Reservoir of Antibiotic Resistance Genes in Dairy Farms - Salerno, Barbara; Cornaggia, Matteo; Sabatino, Raffaella; Di Cesare, Andrea; Furlan, Maddalena; Barco, Lisa; Orsini, Massimiliano; Cordioli, Benedetta; Mantovani, Claudio; Bano, Luca; Losasso, Carmen (Frontiers in Public Health, 2022)
A side effect of antibiotics usage is the emergence and dissemination of antibiotic resistance genes (ARGs) within microbial communities. The spread of ARGs among pathogens has emerged as a public health concern. While the distribution of ARGs is documented on a global level, their routes of spreading have not been clarified yet; for example it is not clear whether and to what extent the emergence of ARGs originates in farms, following the selective pressure exerted by antibiotics usage in animal husbandry, and if they can possibly spread into the environment. Here we address this cutting edge issue by combining data regarding antimicrobial usage and quantitative data from selected ARGs (blaTEM, blaCTXM, ermB, vanA, qnrS, tetA, sul2, vanA, mcr-1, ermB, blaCTXM and tetA) encoding for resistance to penicillines, macrolides-lincosamides-streptogramines, glycopeptides, quinolones, tetracyclines, sulphonamides and colistin at farm level. Results suggestunequivocally demonstrate that dairy farms could be considered hotspot of ARGs, comprising those classified as at highest risk for human health, and that a correlation between the usage of penicillins and blaTEM abundances existed, meaning that, although the antibiotic administration is not the exclusive, it remains a certain cause of the ARGs selection and spread in farms. Furthermore, this study identified the undeniable role of calves as the main source of ARGs spread in dairy farms, claiming for targeted actions on this productive category to decrease the load of ARGs along the production chain.